Control of atmospheric particles on diffuse radiation and terrestrial plant productivity: a review - Kanniah, Kasturi Devi (2012)
Terrestrial plant productivity tends to increase under increasing but non-saturating photosynthetically active solar radiation when water, temperature and nutrients are not limiting. However, studies have shown that photosynthesis can also be higher under enhanced diffuse light despite a decrease in total irradiance. Clouds and atmospheric aerosols are two important variables that determine the total and proportion of diffuse light reaching the surface and thereby the rate of photosynthesis and carbon accumulation in plants. In addition to these factors, the response of plants to diffuse radiation is also dependant on plant characteristics such as functional types, leaf physiology, leaf area, leaf inclination, canopy structure and shape (i.e. clumping). Local environmental conditions (i.e. temperature, soil moisture, vapour pressure deficit, etc.) then modulate these plant responses. Changes in solar radiation as a consequence of clouds and aerosols thus can modify the carbon balance of terrestrial ecosystems. Therefore, understanding the role of solar radiation in terrestrial carbon processes has become one of the goals in terrestrial carbon cycle studies. It can help to identify the control and mechanisms of carbon processes and determines the geographical and temporal distribution of the major pools and fluxes in the global carbon cycle. Here we review the role of clouds and aerosols in partitioning solar radiation and their interactions with carbon processes of terrestrial plants. We also focus our review on vegetation characteristics that control the impact of radiation partitioning on vegetation carbon processes and the role of modelling approach to study this impact. We identify gaps in this field of research and further propose recommendations to bridge the gap.